Advanced maternal age: copy number variations and pregnancy outcomes - Cao, Luoyuan; Dong, Wenxu; Wu, Qinjuan; Huang, Xiaomin; Zeng, Xiaomei; Yang, Jing; Lu, Jiaojiao; Chen, Xunyan; Zheng, Xian; Fu, Xianguo (Frontiers in Genetics, 2023)
Objective: Adverse pregnancy outcomes are closely related to advanced maternal age (AMA; age at pregnancy ≥35 years). Little research has been reported on aneuploid abnormalities and pathogenic copy number variations (CNVs) affecting pregnancy outcomes in women with AMA. The purpose of this study was to assess CNVs associated with AMA in prenatal diagnosis to determine the characteristics of pathogenic CNVs and assist with genetic counseling of women with AMA. Methods: Among 277 fetuses of women with AMA, 218 (78.7%) were isolated AMA fetuses and 59 (21.3%) were non-isolated AMA fetuses and showed ultrasound anomalies from January 2021 to October 2022. Isolated AMA was defined as AMA cases without sonographic abnormalities. Non-isolated AMA was defined as AMA cases with sonographic abnormalities such as sonographic soft markers, widening of the lateral ventricles, or extracardiac structural anomalies. The amniotic fluid cells underwent routine karyotyping followed by single nucleotide polymorphism array (SNP-array) analysis. Results: Of the 277 AMA cases, karyotype analysis identified 20 chromosomal abnormalities. As well as 12 cases of chromosomal abnormalities corresponded to routine karyotyping, the SNP array identified an additional 14 cases of CNVs with normal karyotyping results. There were five pathogenetic CNVs, seven variations of uncertain clinical significance (VOUS), and two benign CNVs. The detection rate of abnormal CNVs in non-isolated AMA cases was increasing (13/59; 22%) than in isolated AMA cases (13/218; 5.96%) (p < 0.001). We also determined that pathogenic CNVs affected the rate of pregnancy termination in women with AMA. Conclusion: Aneuploid abnormalities and pathogenic CNVs affect pregnancy outcomes in women with AMA. SNP array had a higher detection rate of genetic variation than did karyotyping and is an important supplement to karyotype analysis, which enables better informed clinical consultation and clinical decision-making.